Association between sequevar and antibiotic treatment outcome in patients withMycobacterium abscessuscomplex infections in Japan. Issue 1 (January 2018) - Yoshida, Shiomi; Tsuyuguchi, Kazunari; Kobayashi, Takehiko; Tomita, Motohisa; Inoue, Yoshikazu; Hayashi, Seiji; Suzuki, Katsuhiro
Abstract : Purpose. : Macrolide susceptibility differs between subspecies in the Mycobacterium abscessus complex, likely due to differences in erm (41) sequevars. Patients with M. abscessus complex infection generally show poor clinical outcomes in response to antibiotic treatment. Here, the association between genotype and treatment outcome was investigated. Methodology. : We collected 69 isolates from 35 patients with non‐cystic fibrosis bronchiectasis: 24 had M. abscessus complex lung disease and non‐cystic fibrosis bronchiectasis, and 11 were colonized. Outcome analysis was performed in the 24 infected patients. Molecular analyses, including erm (41) and rrl sequencing, and variable‐number tandem‐repeat (VNTR) analysis of 69 isolates, from 24 infected and 11 colonized patients, were performed to elucidate the influence of genotype on antibiotic susceptibility. Results. : Among the 24 patients, 18 (14 infected with M. abscessus subsp. abscessus and 4 with M. abscessus subsp. massiliense ) showed unfavourable outcomes; six (three infected with M. abscessus subsp. abscessus and three with M. abscessus subsp. massiliense ) exhibited favourable outcomes. Patients with unfavourable outcomes showed acquired clarithromycin resistance (33.3 vs 0 %), mixed sequevars (38.9 vs 16.7 %) and differing VNTR patterns between initial and serial isolates (33.3 vs 16.7 %). In contrast, in the 11 colonized patients, M. abscessus subsp. abscessus C28 (sequevar 02) and M. abscessus subsp. massiliense were the most prevalent subspecies. Conclusion. : Patients infected with multiple sequevars and genotypes were more likely to exhibit treatment failure and/or recurrence. The precise identification of subspecies and analyses of mycobacterial characteristics may help to predict treatment outcomes in patients with M. abscessus complex lung disease.